Implementasi Sistem Pengupahan Pekerja Dalam Perspektif Ekonomi Islam (Studi Kasus Pada Konveksi Lizdian 94) - Rachmawati, Rachmawati (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2026)
Wages are a crucial aspect of industrial relations, as many wage practices do not yet reflect the principles of justice from an Islamic perspective. This discrepancy often gives rise to social issues, including feelings of injustice among workers. Islam explicitly rejects all forms of discrimination and injustice against workers. This study aims to examine the labor wage system from an Islamic economic perspective, using a case study at the Lizdian 94 Convection. This study used a qualitative descriptive method with a normative and sociological approach, and is categorized as field research. Data were obtained through interviews as a primary source and supporting literature as a secondary source. The results indicate that the wage system at the Lizdian 94 Convection complies with sharia provisions in determining the amount and timing of wage payments. However, the aspect of proportional justice has not been fully implemented, as there is no wage differentiation that reflects the level of responsibility and workload of each position. Nevertheless, in general, the wages provided are considered adequate and able to meet the basic needs of workers.  Keywords: Wages, Discrimination, Workers, Islam.